Dual redox effects of 2,6-bis-(4-hydroxyl-3-methoxybenzylidene) cyclohexanone (BHMC) on human liver cancer cells, HepG2 via ROS, glutathione and Nrf2/Keap1 pathway - Mohd Shafiee, Muhammad Aminuddin; Syed Alwi, Sharifah Sakinah; Othman, Zulkefley; Nurdin, Armania; Md Razip, Nurliyana Najwa (Nature Research, 2025)
Introduction: Curcumin has demonstrated significant potential as a chemoprotective agent by inducing death in malignant cells while exhibiting selective cytotoxicity toward normal cells. However, curcumin has limited bioavailability which hindered its full potential. Thus, 2,6-bis-(4-hydroxyl-3-methoxybenzylidene) cyclohexanone (BHMC), a curcuminoid derivative is produced by eliminating unstable β-diketone component, transformed it with double bonds while retaining the phenolic hydroxyl group. Of note, BHMC triggers greater cytotoxic effect via inducing higher oxidative stress damage through reactive oxygen species (ROS)-mediated pathway. Increased of ROS cause the redox buffering system to collapse, resulting in lipid peroxidation and disintegration of the mitochondrial membrane potential, which eventually causes cell death in malignant cells. Methodology: Total antioxidant activity was determined using Ferric Reducing Antioxidant Power (FRAP) assay biochemically and on HepG2 cells. Intracellular ROS was then measured using 2′,7′-Dichlorodihydrofluorescein diacetate (DCFDA) assay which was confirmed by determined the level of intracellular glutathione. The expression of Keap1 and Nrf2 was further analysed using immunocytochemistry. Result and Discussion: BHMC exhibits antioxidant properties by demonstrating greater total antioxidant activity both biochemically and in HepG2 cells. Further analysis shows that BHMC significantly reduces intracellular ROS levels in HepG2 cells at low concentrations of 15 µM after 18 h and 10 µM after 24 h compared to untreated. However, at a higher concentration of 20 µM, BHMC induces oxidative stress like curcumin by lowering the ratio of reduced glutathione to glutathione disulfide (GSH/GSSG) and upregulating Nrf2 expression. The effects of BHMC are dose-dependent, with the compound acting as either an antioxidant or pro-oxidant depending on the concentrations. Conclusion: BHMC exhibits potent antioxidant activity by reducing harmful reactive oxygen species and boosting protective glutathione levels in cells at low doses, but at higher doses, it may induce oxidative stress. These findings suggest BHMC’s dose-dependent role in balancing antioxidant and pro-oxidant effects, highlighting its potential for further therapeutic exploration.